Tuwim: Years After - Węgrzyniak, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The subject of the article is to present an outline of the reception of Julian Tuwim’s works in the last decade. “The Prince of Poets” of the interwar period, well known in the post-war era, is less and less known today. Post-war generations of poets made no particular references to Tuwim and his poetry, and even though many critical works are being published about him, Tuwim’s works do not engage critics who would be able to reconnect his writing with the contemporary world. Tuwim is disappearing from school literary curricula, contemporary readers remember only his children’s poems and one can doubt whether this situation can be changed by an extensive, multifaceted work by Piotr Matywiecki Twarz Tuwima (Tuwim’s face), the comprehensive and readable biography of the poet. It is an important book which tackles a number of vital questions concerning for instance the tragic alienation of the Polish Jew who lived between two cultures and wanted to be excluded from neither.